Vertical jump performance and blood ammonia and lactate levels during typical training sessions in elite 400-m runners - Gorostiaga, E. M.; Asiain, X.; Izquierdo, M.; Postigo, A.; Aguado, R.; Alonso, J. M.; Ibanez, J. (The Journal of Strength and Conditioning Research, 2010)
This study described the effects of 6 typical high-intensity intermittent running training sessions of varying distances (60-300 m) and intensities (80-105% of the individual best 400-m record time) on blood ammonia and lactate concentration changes and on vertical jumping height, in twelve 400-m elite male runners. At the end of the training sessions, similar patterns of extremely high blood lactate (14-23 mmol/L) and ammonia levels (50-100 µmol/L) were observed. Vertical jumping performance was maintained during the initial exercise bouts up to a break zone of further increase in the number of exercise bouts, which was associated, especially in subjects with the highest initial vertical jump, with a pronounced decrease (6-28%) in vertical jumping performance, as well as with blood lactate concentrations exceeding 8-12 mmol/L, and blood ammonia levels increasing abruptly from rest values. This break zone may be related to signs of energetic deficiency of the muscle contractile machinery associated with the ability to regenerate adenosine triphosphate at high rates. It is suggested that replacing some of these extremely demanding training sessions with other intermittent training sessions that preserve muscle generating capacity should allow elite athletes to practice more frequently at competitive intensity with lower fatigue.